Association between amyloid-beta deposition and cortical thickness in dementia with Lewy bodies. (April 2023) - Chin, Kai Sin; Gajamange, Sanuji; Desmond, Patricia M; Villemagne, Victor L; Rowe, Christopher C; Churilov, Leonid; Yassi, Nawaf; Watson, Rosie
Objective: Amyloid-beta often co-exists in dementia with Lewy bodies, but its clinical relevance in dementia with Lewy bodies remains unclear. This study aimed to investigate the clinical and imaging correlates of amyloid-beta deposition in dementia with Lewy bodies, particularly its relationship with cortical thickness in Alzheimer's disease–prone regions and hippocampal volume. Methods: Twenty-four participants with probable dementia with Lewy bodies underwent high-resolution magnetic resonance imaging and amyloid-beta positron emission tomography imaging using the radiotracer 18 F-NAV4694. Amyloid-beta deposition was quantified and reported using the Centiloid method. Results: Amyloid-beta positivity, defined as Centiloid > 50, was present in 45.8% of dementia with Lewy bodies participants. There were no statistically significant differences in clinical characteristics between Aβ+ and Aβ− dementia with Lewy bodies. Compared with the Aβ− group, Aβ+ dementia with Lewy bodies exhibited greater global cortical thinning as well as in the Alzheimer's disease–prone region of interest, adjusted for age, sex and years of education. A mean cortical thickness of 5.12 mm across a combined meta-region of interest has a sensitivity of 88.9% and specificity of 90.0% in discriminating Aβ+ from Aβ− dementia with Lewy bodies. Hippocampal volume was not different between groups. Conclusion: Early structural changes in cortical thickness, but not hippocampal volume, were observed in dementia with Lewy bodies with significant amyloid-beta burden. This may represent an early Alzheimer's disease–related neurodegenerative process.